Inovasi Media Pembelajaran Sejarah: Studi Eksperimen Menggunakan Permainan Ular Tangga - Novadilla, Elsa Firanty; Susanti, Retno (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to examine the effectiveness of the snakes and ladders game in history learning. The background of this study is to create a more interactive and enjoyable learning atmosphere, so that history lessons are more enjoyable for students. This study used a quasi-experimental method with a non-equivalent control group design. The research subjects were divided into two groups, namely the experimental class using the snakes and ladders media and the control class using conventional methods. Data were collected through multiple-choice tests and analyzed using t-tests to measure differences in learning outcomes. The results showed a significant difference in learning outcomes between the two classes. The increase in student learning outcomes in the experimental class was much higher than in the control class. Thus, it can be concluded that the snakes and ladders game media is effective as an innovation in history learning.